1989
DOI: 10.1007/bf00442565
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine in the treatment of 121 out-patients

Abstract: Retrospectively, effects of long-term therapy with clozapine were evaluated in 121 out-patients. They were treated for 32 +/- 43 months in a daily dosage of 131 +/- 99 mg. Sixty nine patients were schizophrenic and had previously received one or more neuroleptics but with insufficient response or severe side effects. Nine patients suffered from tardive dyskinesia (TD), 44 patients had other diagnoses. Twenty two per cent of the schizophrenic patients improved slightly, 65% markedly and in 13% the symptoms near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 6 publications
1
29
0
2
Order By: Relevance
“…Case reports suggested the antidepressant efficacy of clozapine in bipolar (Calabrese et al 1991;Privitera et al 1993;Suppes et al 1994) and unipolar (Leppig et al 1989;Naber et al 1992;Ranjan and Meltzer 1996) patients. No open-label or controlled data are available with the use of clozapine in bipolar depression.…”
Section: Clozapinementioning
confidence: 99%
See 2 more Smart Citations
“…Case reports suggested the antidepressant efficacy of clozapine in bipolar (Calabrese et al 1991;Privitera et al 1993;Suppes et al 1994) and unipolar (Leppig et al 1989;Naber et al 1992;Ranjan and Meltzer 1996) patients. No open-label or controlled data are available with the use of clozapine in bipolar depression.…”
Section: Clozapinementioning
confidence: 99%
“…Clozapine has been suggested to be effective in the long-term management of treatment-resistant bipolar patients in case reports (Calabrese et al 1991;Frankenburg 1993;Suppes et al 1994;Puri et al 1995;Frye et al 1996;Calabrese and Gajwani 2000) and in open-label studies (Battegay et al 1977;Leppig et al 1989;McElroy et al 1991;Banov et al 1994;Frankenburg and Zanarini 1994;Calabrese et al 1996;Ciapparelli et al 2000), in most cases used as an adjunctive agent (Table 5). In the study by Calabrese et al (1996), among 11 bipolar patients taking clozapine monotherapy, increasing clozapine dose was sufficient to manage the re-emergence of manic symptoms in 5 of them, whereas coadministration of antidepressants was needed to treat major depression in 5 of them.…”
Section: Clozapinementioning
confidence: 99%
See 1 more Smart Citation
“…There have been reports that conventional antipsychotics are used in around one-third of patients receiving clozapine in some European countries. 51,52 For example, McCarthy and Terkelsen 53 reported that a conventional antipsychotic was added to clozapine in 30-35% of cases in Denmark. This is despite the lack of convincing research evidence to justify the addition of another antipsychotic in patients with only a partial response to clozapine monotherapy.…”
Section: Combined Antipsychoticsmentioning
confidence: 99%
“…Atypical antipsychotics such as clozapine, olanzapine, risperidone or quetiapine are considered as relatively safe alternatives used as add-on med- Hummel/Dittmann/Forsthoff/Matzner/ Amann/Grunze ication in the maintenance treatment of bipolar and schizoaffective disorders [9]. Hints at efficacy of clozapine in schizoaffective [10][11][12] and bipolar disorders [13][14][15] were reported by several authors. However, controlled trials of clozapine in maintenance treatment are still missing.…”
Section: Introductionmentioning
confidence: 99%